ASSESSING COMPARABILITY IN SUSTAINABILITY REPORTS: A MULTI-LEVEL ANALYSIS IN THE OIL AND GAS INDUSTRY OF A DEVELOPING ECONOMY - Rehman, Hania (PEOPLE: International Journal of Social Sciences, 2024)
Purpose - The usefulness of sustainability reports in meeting the information needs of stakeholders is questionable due to information asymmetry resulting from the proliferation of sustainability reporting frameworks. Despite this, arguments have surfaced that intra-industry firms, due to shared characteristics, might achieve a semblance of comparability. This study endeavors to analyse the comparability of sustainability information of organisations in the oil and gas industry of a developing economy. Design/methodology/approach - To achieve the study purpose, a content analysis of sustainability information was performed by identifying the framework, structure, and content used to disclose sustainability information, using GRI reporting standards as a reference for comparability. Findings - The analysis revealed that at a framework level, most organisations do not use any international sustainability reporting frameworks, opting for discretion. Regarding structural aspects, sustainability information lacks comparability owing to disparate sections. At a content level, the economic indicators have the highest compliance than social and environmental indicators, highlighting inconsistent reporting to different groups of stakeholders. Originality – The novelty of this research lies in its comprehensive exploration of comparability of sustainability reports across multiple levels with specific emphasis on the environmentally sensitive oil and gas industry within the framework of a developing economy.